STUDI PENGEMBANGAN USAHATANI KELAPA SAWIT RAKYAT DI DESA GEDUNG AGUNG KECAMATAN DESA GEDUNG AGUNG KECAMATAN KIKIM TIMUR KABUPATEN LAHAT - Saputra, Julian; Abubakar, Rafeah; Iswarini, Harniatun (Societa: Jurnal Ilmu-Ilmu Agribisnis, 2016)
Study of palm oil farming development in gedung agung village of the kikim timur lahat district. This study aims determine how the development of palm oil farming in the Gedung Agung village of the Kikim Timur Lahat District. This study was conducted in January through march 2016. The method used is a survey method, methods of sampling done by simple random sampling. Data collection methods used in this study is the observation and direct interviews with respondents who have been determinet by using tools like questionnaire that has been prepared in advance. Data processing is done descriptif research results. The results showed that strengths development of farming oil palm is the experience of farmers in farming oil palm, where the land is located, the availability of capital and the price of TBS stable, weaknesses in the development of farming oil palm is the lack of knowledge and information on the development of farming coconut palm, ownership of land is narrow, capital of small farms and use of seeds of wild, opportunities in the development of farming oil palm is in increasing the opinions of farmers, the potential utilization of idle land, the prospect of their loan fund money as the KUD and the use of quality seeds and threats in the development of palm oil farming is a lot of its emerging private oil Palm plantations, lack of knowledge and skills of farmers in doing farming oil palm plantations that they had. If at any time the rainy season the oil palm plantations where inundate by water.